Increases in intracellular calcium via activation of potentially multiple phospholipase C isozymes in mouse olfactory neurons - Szebenyi, Steven A.; Ogura, Tatsuya; Sathyanesan, Aaron; AlMatrouk, Abdullah K.; Chang, Justin; Lin, Weihong (Frontiers in Cellular Neuroscience, 2014)
Phospholipase C (PLC) and internal Ca2+ stores are involved in a variety of cellular functions. However, our understanding of PLC in mammalian olfactory sensory neurons (OSNs) is generally limited to its controversial role in odor transduction. Here we employed single-cell Ca2+ imaging and molecular approaches to investigate PLC-mediated Ca2+ responses and its isozyme gene transcript expression. We found that the pan-PLC activator m-3M3FBS (25 µM) induces intracellular Ca2+ increases in vast majority of isolated mouse OSNs tested. Both the response amplitude and percent responding cells depend on m-3M3FBS concentrations. In contrast, the inactive analog o-3M3FBS fails to induce Ca2+ responses. The m-3M3FBS-induced Ca2+ increase is blocked by the PLC inhibitor U73122, while its inactive analog U73433 has no effect. Removal of extracellular Ca2+ does not change significantly the m-3M3FBS-induced Ca2+ response amplitude. Additionally, in the absence of external Ca2+, we found that a subset of OSNs respond to an odorant mixture with small Ca2+ increases, which are significantly suppressed by U73122. Furthermore, using RT-PCR and real-time quantitative PCR, we found that multiple PLC isozyme gene transcripts are expressed in olfactory turbinate tissue in various levels. Using RNA in situ hybridization analysis, we further show expression of β4, γ1, γ2 gene transcripts in OSNs. Taken together, our results establish that PLC isozymes are potent enzymes for mobilizing intracellular Ca2+ in mouse OSNs and provide molecular insight for PLC isozymes-mediated complex cell signaling and regulation in the peripheral olfactory epithelium.